Remote Sensing Advances for Earth System Science The ESA Changing Earth Science Network: Projects 2011-2013 - Fernández-Prieto, Diego; Sabia, Roberto (Springer Earth System Sciences, 2016)
This book presents cutting-edge remote sensing research, outlining the advanced use of European Space Agency (ESA) satellite data in the context of climate change. The ESA, through its Support to Science Element (STSE) Programme, funds a network of young post-doc scientists pursuing 2-year cutting-edge research projects in the field of remote sensing. This "Changing Earth Science Network" focuses on the exploitation of Earth Observation (EO) data to address major issues concerning the broader context of climate change in five scientific research domains: the oceans, atmosphere, cryosphere, land and solid earth.